Avaliação de ASPECTOS EVOLUTIVOS DA RESPOSTA IMUNE ASSOCIADA periodontite com doenças cardiovasculares - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2015)
Periodontal diseases are chronic conditions infectius inflammatory, multifactorial, which has the biofilm its primary etiology, affects 70% of the population and may influence the overall health of the body. Another inflammatory disease with a high incidence rate and that has become a public health problem is atherosclerosis. Authors suggest that systemic exposure to infections may result in the release of inflammatory cytokines, which alter lipid metabolism, promotes hyperlipidemia, hyperglycemia and lipid oxidation; acting as a risk factor for cardiovascular disease (CVD). This study analyzed levels of blood components; conducting a comparative analysis of data obtained through laboratory tests and plasma analysis of oxidized LDL. This study included 60 volunteer patients. And, 30 patients with a history of CVD were from the Intermunicipal Consortium of Health (CIS) 5th Regional Health Center West of Paraná; all in treatment. And 30 without CVD were from the dental clinic SMM They were divided into 4 groups. Group SS 15 patients without PD and without CVD (control). Group CC 15 patients with PD and CVD. Group CS 15 PD patients without CVD. Group SC 15 patients without PD and CVD. It was considered p <0.05. No significant differences were observed for leukocyte, platelets, HDL, triglycerides index and quantitation of oxidized cholesterol between groups. The CC group showed the lowest total cholesterol index with a significant difference with the CS group p = 0.0247. For LDL levels the lowest index was presented by the CC group with significant differences with CS groups p = 0.0147 and SC p = 0.0359. Significant differences were also found in the glucose index where the CC group had the highest rate among the groups with significant differences with CS p = 0.0259 and p SS groups = 0.0043.
Keywords: periodontite; aterosclerose; biofilme; citocinas; colesterol; periodontitis; atherosclerosis; Plaque; Cytokines; Cholesterol; CNPQ::CIENCIAS BIOLOGICAS